2002
DOI: 10.1006/jado.2002.0496
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a comprehensive AIDS education curriculum in Hungary – the role of good educators

Abstract: The aim of this research was to evaluate a school-based AIDS education programme in Eastern Europe. Four evaluation segments were undertaken: process and outcome evaluations of the training of AIDS educators and of the educational activities for students. While most AIDS education curricula focus on the content of the education, our findings demonstrate that other aspects--including the characteristics of those educators who appear to be most effective, the way in which education is affected by teachers' attit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 10 publications
(9 reference statements)
1
7
0
Order By: Relevance
“…Studies have shown that training helps improve knowledge, attitudes, and readiness of teachers to impart HIV/AIDS-prevention information to their students [13,26,27]. The findings of the present study also revealed that the study teachers had gathered comprehensive knowledge on HIV/AIDS through the cascading training program, which they did not have before.…”
Section: Discussionsupporting
confidence: 48%
“…Studies have shown that training helps improve knowledge, attitudes, and readiness of teachers to impart HIV/AIDS-prevention information to their students [13,26,27]. The findings of the present study also revealed that the study teachers had gathered comprehensive knowledge on HIV/AIDS through the cascading training program, which they did not have before.…”
Section: Discussionsupporting
confidence: 48%
“…Teachers are in daily contact with pupils and are familiar with the schools' organization. As is evident from prior studies, teachers are key to the development, implementation, evaluation, and, therefore, success of health education interventions (16)(17)(18)(19). Moreover, teachers with greater competence in delivering skills-based health education could improve students' health and protective behaviors (20)(21)(22) while reducing risk behaviors (20,23).…”
Section: Discussionmentioning
confidence: 97%
“…Support for teachers is important for this to occur. The significance of teachers in school health promotion is discussed in greater detail elsewhere (St Leger, 1998;Kinsman et al, 2001;Gyarmathy et al, 2002;Midford et al, 2002).…”
Section: Involving the School And Local Communitiesmentioning
confidence: 99%